2005
DOI: 10.1002/elps.200500304
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate optimization approach for chiral resolution of drugs using human serum albumin in affinity electrokinetic chromatography-partial filling technique

Abstract: The enantiomeric resolution of chiral compounds using HSA by means of affinity EKC (AEKC)-partial filling technique is the result of a delicate balance between different experimental variables such as protein concentration, running pH (background electrophoretic buffer, protein and compound solutions) and protein solution plug length. In this paper multivariate optimization approaches for chiral separation of four basic drugs (alprenolol, oxprenolol, promethazine and propranolol) using HSA as chiral selector i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Three publications by Martinez-Gomez et al [171][172][173] utilized HSA as a chiral selectand (affinity EKC) during the review period. The first report detailed the separation of oxprenolol enantiomers [171].…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Three publications by Martinez-Gomez et al [171][172][173] utilized HSA as a chiral selectand (affinity EKC) during the review period. The first report detailed the separation of oxprenolol enantiomers [171].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The highest resolution was 1.47 and the method was applied to commercial product analysis. The second study was expanded to include three additional chiral pharmaceuticals (alprenolol, propranolol, and promethazine) and multivariate optimization (Box-Behnken) [172]; pH, selector concentration, HSA plug length, and their cross-products were examined through experimental design (pareto charts, partial least squares regression, and multiple linear regressions performed) to increase resolution. Hydrophobic analytes required lower HSA concentrations and smaller plug lengths, whereas the opposite was found for more hydrophilic compounds.…”
Section: Miscellaneousmentioning
confidence: 99%
“…It has been found that for the current system Amberlite TM IRP 69 / Propranolol HCl, the pH value in the drug solution is 6 and does not change -within experimental error -during the course of the experiments (data not shown). As the pK A value of PropH + is 9.45 [17], it is concluded that the drug persists mainly in its ionic form during experiments, and that the pH would not need special attention.…”
Section: Amberlitementioning
confidence: 99%
“…The pK A value of PropH + is 9.45 [23], and all the solutions handled during experiments were in the pH range of between 5.9 and 6.3, which accounts for more than 99.9% of the molecules being dissociated. Moreover, chloride-ions are not considered to take part in the exchange process due to repulsive forces between chloride ions and the electric potential difference barrier (Donnan potential) which repel the co-ions from the ion exchanger.…”
Section: Concentrations Of Solutionsmentioning
confidence: 99%